Medical Stock Management System (MeDSys) - Noor Hidayah , Harun (UTeM, 2009)
Medical Stock Management System or MeDSys is being developed to manage the medical stock or inventory for this system obviously for a small kind industry that are in under develop and also required a small budget small industry. Delivering the high levels of reliability and availability required of MeDSys required not only great technology but also great operational processes. Building a scalable, highly available system is a necessary process in becoming functional successful. MeDSys is being developed to give convenience to the doctor and the medical officer. Due to the existing system is still manual, it has caused some problems, such as face some difficulties in finding certain information and take too long in searching some files because of the disorder management and supervision. This suggested system is focuses on manage the stock transaction and record all the medical suppliers / vendors for the clinic. This system is allow the user to do the maintenance of the system by add, delete and modify the data to the database. The methodology that use in developing this project is waterfall model. The waterfall model derives its name due to the cascading effect from one phase to the other. This project is also using the object-oriented approach to develop system. Software that uses to manage the database is Microsoft Access while the using of Microsoft Visual Studio.NET is to build a dynamic system and all the documentation is proposed by using Microsoft Office. Hopefully this system can meet the user requirements and make the system management smoothly.